Differential Neuronal Plasticity of Dental Pulp Stem Cells From Exfoliated Deciduous and Permanent Teeth Towards Dopaminergic Neurons. Issue 9 (4th February 2016) - Majumdar, Debanjana; Kanafi, Mohammad; Bhonde, Ramesh; Gupta, Pawan; Datta, Indrani
Abstract : Based on early occurrence in chronological age, stem‐cells from human exfoliated deciduous teeth (SHED) has been reported to possess better differentiation‐potential toward certain cell‐lineage in comparison to stem‐cells from adult teeth (DPSCs). Whether this same property between them extends for the yield of functional central nervous system neurons is still not evaluated. Hence, we aim to assess the neuronal plasticity of SHED in comparison to DPSCs toward dopaminergic‐neurons and further, if the difference is reflected in a differential expression of sonic‐hedgehog (SHH)‐receptors and basal‐expressions of tyrosine‐hydroxylase [TH; through cAMP levels]. Human SHED and DPSCs were exposed to midbrain‐cues [SHH, fibroblast growth‐factor8, and basic fibroblast growth‐factor], and their molecular, immunophenotypical, and functional characterization was performed at different time‐points of induction. Though SHED and DPSCs spontaneously expressed early‐neuronal and neural‐crest marker in their naïve state, only SHED expressed a high basal‐expression of TH. The upregulation of dopaminergic transcription‐factors Nurr1, Engrailed1, and Pitx3 was more pronounced in DPSCs. The yield of TH‐expressing cells decreased from 49.8% to 32.16% in SHED while it increased from 8.09% to 77.47% in DPSCs. Dopamine release and intracellular‐Ca 2+ influx upon stimulation (KCl and ATP) was higher in induced DPSCs. Significantly lower‐expression of SHH‐receptors was noted in naïve SHED than DPSCs, which may explain the differential neuronal plasticity. In addition, unlike DPSCs, SHED showed a down‐regulation of cyclic adenosine‐monophosphate (cAMP) upon exposure to SHH; possibly another contributor to the lesser differentiation‐potential. Our data clearly demonstrates for the first time that DPSCs possess superior neuronal plasticity toward dopaminergic‐neurons than SHED; influenced by higher SHH‐receptor and lower basal TH expression. J. Cell. Physiol. 231: 2048–2063, 2016. © 2016 Wiley Periodicals, Inc.